British politics : a very short introduction - Wright, Anthony, 1948- (Oxford : Oxford University Press, 2020)
The nature of politics in Britain is being questioned as never before, with Brexit throwing both party and national politics into turmoil. Here, Tony Wright provides the essential context for current debates about the state of British politics, identifying key characteristics of its history and ideas which influence the current political landscape.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on June 2, 2020).
Keywords: Politics, Practical -- Great Britain; Great Britain -- Politics and government